Multimorbidity is associated with lower total 24-hour movement activity among US adults - Dooley, Erin E.; Chen, Ligong; Ghazi, Lama; Hornikel, Bjoern; Martinez-Amezcua, Pablo; Palta, Priya; Bowling, C. Barrett; Muntner, Paul; Lewis, Cora E.; Pettee Gabriel, Kelley (Preventive medicine reports, 2023)
•Dose-response relation with number of chronic conditions and lower daily movement.•Adults with complex multimorbidity were least active throughout the day.•Multimorbidity may further accelerate age-related declines in physical activity.•Multimorbidity status may be helpful to identify adults at risk for low movement. Having chronic conditions may result in reduced physical and cognitive function but less is known about multimorbidity with daily movement. We examined the association of multimorbidity and device-measured total daily movement in a nationally representative sample of US adults aged ≥ 30 years from the 2011–2014 National Health and Nutrition Examination Surveys. Any multimorbidity (≥2 conditions) and complex multimorbidity (≥3 conditions across ≥ 3 body systems) were quantified using 16 chronic conditions via self-report and/or clinical thresholds. Total movement over 24-hours (Monitor-Independent Movement Summary units [MIMS-units]) was measured using a wrist-worn device (ActiGraph GT3X). Multivariable linear regression examined the association of 1) each chronic condition, 2) number of conditions, 3) any multimorbidity, and 4) complex multimorbidity with total movement. Covariates included age, gender, race/ethnicity, educational attainment, and smoking status. Among US adults (N = 7304, mean age: 53.2 ± 0.34 years, 53.2% female, 69.4% Non-Hispanic White), 62.2% had any multimorbidity with 34.2% having complex multimorbidity. After adjustment, a higher number of chronic conditions was associated with incrementally lower total movement (β MIMS-units [95% CI] compared to those with no chronic conditions; one: −419 [−772, −66], two: −605 [−933, −278], three: −1201 [−1506, −895], four: −1908 [−2351, −1465], 5+: −2972 [−3384, −2560]). Complex multimorbidity presence was associated with −1709 (95% CI: −2062, −1357) and −1269 (−1620, −918) lower total movement compared to those without multimorbidity and multimorbidity but not complex, respectively. Multimorbidity was associated with lower 24-h movement among US adults and may be helpful for identifying adults at risk for low movement.